Morphological and molecular characterization of Lobophora declerckii and L. variegata (Dictyotales, Ochrophyta) on the Atlantic coast of Mexico - Godínez-Ortega, José Luis; Cabrera, Lidia I.; García-Sandoval, Ricardo; Wynne, Michael J.; Olivares-Rubio, Hugo F.; Ramírez-García, Pedro; Granados-Barba, Alejandro (Phytotaxa, 2018)
The Veracruz Reef System National Park (PNSAV) is located in the central region of Veracruz, off the coast of the municipalities of Veracruz, Boca del Río and Antón Lizardo. It is a complex and important system within the Gulf of Mexico, since it has been declared a biosphere reserve by UNESCO, a Ramsar wetland and an essential component of the southwestern Gulf of Mexico Reef Corridor. Lobophora contains 28 currently recognized species and has a pantropical distribution that includes the Atlantic, Pacific, and Indian Oceans in both hemispheres. Recently, some species have been identified from Western Atlantic Ocean, mainly in the Caribbean Sea. However, very little is known about Lobophora species diversity on the Mexican coast. In this study, morphological and molecular analyses (MAAT) using cytochrome c oxidase 3 (COX3) sequences as a barcode gene were used to study Lobophora spp. The results indicate that there are two species on the Mexican coasts, Lobophora declerckii and L. variegata. Lobophora declerckii represents a new record for the southwest of the Gulf of Mexico and, the presence of L. variegata was confirmed for the Mexican Caribbean.